Community energy: design recommendations for the integration of distributed renewable energy generation into existing urban neighborhoods - Schneider, Thomas (Kansas State University, 2021)
The current American energy system is being pushed beyond its limits and is not suited to address contemporary energy issues (Crabtree et al. 2011). Existing literature indicates that small-scale, distributed energy production is needed to address the shortcomings of current energy infrastructure (Yoldas et al. 2017). In the coming decades, grid modernization projects (solar production, micro-wind production, and battery storage) have the potential to significantly alter existing neighborhoods. Current research focuses primarily on technical considerations and does not substantially address the physical footprint of grid modernization within an existing community. As communities begin to consider the future of their energy systems, landscape architects can position themselves as facilitators to establish a community-driven transition to renewable energy. This research looks to identity how landscape architects can address the physical footprint and visual impact of renewable energy production in an urban setting. A two-part methodology was developed consisting of (1) site observation and mapping, and (2) community interviews. Site observation and mapping was utilized to define an initial study area. A study site selection procedure identified the Ivanhoe Southeast neighborhood for further study. Residents of the Ivanhoe Southeast neighborhood were engaged in semi-structured interviews, using photo boards, to understand how individuals perceive the visual impact and physical footprint of solar production, micro-wind production, and battery storage in an urban setting. Social data collected during the community interviews was then passed through a thematic coding procedure to identify key themes within the data. Themes of identity, aesthetics, function, proximity, education, and interest emerged as critical concepts for the incorporation of renewable energy in an urban setting. A series of design recommendations for each of the identified themes were then created, based on the social data collected during the community interviews. Lastly, a conceptual design project was created that applies the design recommendations to the development of a district energy masterplan for the Ivanhoe Southeast neighborhood. This research is intended to engage landscape architects, policy makers, engineers, local leaders, and community members in a dialogue that considers the future energy landscape in urban neighborhoods.
Keywords: Renewable energy; Urban vacancy; Community energy; Microgrid; Climate change